2007
DOI: 10.1590/s0004-27492007000200029
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 cell proliferation in familial and in esporadic unilateral retinoblastoma: case report

Abstract: The familial retinoblastoma, besides the earlier age presentation, showed 45.8% more Ki-67 positive cells than the same stage sporadic one. This proliferation rate may explain the earlier presentation age of the tumor in the inherited disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Complementing with biomarkers has shown to be of benefit in the determination of prognosis of the paediatric patients with RbT. Studies have shown that increased expression of cell proliferation biomarkers such as Ki67 is associated with advanced tumour stage and poor clinical outcomes 13–15. Other tumour markers such as p53 have been found to correlate significantly with the HHRFs including massive choroidal invasion and positive surgical margin of the optic nerve 16…”
Section: Introductionmentioning
confidence: 99%
“…Complementing with biomarkers has shown to be of benefit in the determination of prognosis of the paediatric patients with RbT. Studies have shown that increased expression of cell proliferation biomarkers such as Ki67 is associated with advanced tumour stage and poor clinical outcomes 13–15. Other tumour markers such as p53 have been found to correlate significantly with the HHRFs including massive choroidal invasion and positive surgical margin of the optic nerve 16…”
Section: Introductionmentioning
confidence: 99%